INVESTIGAÇÃO SOBRE A FORMAÇÃO INICIAL E CONTINUADA DOS PROFESSORES DE ENSINO FUNDAMENTAL - Velten, Osmarina A. G.; Dias, Karin B.; Pires, Zailca; Saturno, Camila; Padilha, Cristiane d. S. (Salão do Conhecimento, 2013)
Resumo